BIODEGRADABLE MATERIALS FOR SUSTAINABLE PACKAGING: INNOVATIVE DEVELOPMENTS AND CIRCULAR ECONOMY OPPORTUNITIES (Journal of Medical & Health Sciences Review, 2025)
This research examines the changing dynamics of biodegradable materials for sustainable packaging, highlighting their contribution to the advancement of circular economy principles. Biodegradable polymers, including Polylactic acid (PLA), Polyhydroxyalkanoates (PHAs), natural fiber composites, mycelium-based materials, and algae-derived polysaccharides, present viable alternatives to traditional fossil-based plastics by decomposing into environmentally friendly substances under natural conditions. The analysis incorporates developments in polymer science, biodegradation processes, life-cycle evaluations, and market preparedness, emphasizing innovations such as microbial PHA generation from food and agricultural waste, which enhances the value of residues to mitigate costs and environmental effects. Significant environmental benefits encompass reduce environmental pollution, decreased greenhouse gas emissions, and conformity with Sustainable Development Goals (SDGs), especially in the packaging of the predominant plastic consumer industry. Nonetheless, obstacles include elevated manufacturing expenses, variable degradation rates, material constraints, and insufficient waste treatment infrastructure remain. This interdisciplinary assessment highlights the potential of closed-loop systems to alleviate plastic waste accumulation, resource depletion, and environmental damage by comparing biodegradable alternatives with conventional plastics. Future prospects hinge on scalable technology, policy alignment, and improved feedstocks from waste streams to attain economic feasibility and broad acceptance, hence facilitating a shift towards sustainable and circular packaging solutions.